Combining experimental and computational techniques to understand and improve dry powder inhalers. (2nd January 2022) - Chaugule, V.; Wong, C.Y.; Inthavong, K.; Fletcher, D.F.; Young, P.M.; Soria, J.; Traini, D.
ABSTRACT: Introduction: Dry Powder Inhalers (DPIs) continue to be developed to deliver an expanding range of drugs to treat an ever-increasing range of medical conditions; with each drug and device combination needing a specifically designed inhaler. Fast regulatory approval is essential to be first to market, ensuring commercial profitability. Areas covered: In vitro deposition, particle image velocimetry, and computational modeling using the physiological geometry and representative anatomy can be combined to give complementary information to determine the suitability of a proposed inhaler design and to optimize its formulation performance. In combination, they allow the entire range of questions to be addressed cost-effectively and rapidly. Expert opinion: Experimental techniques and computational methods are improving rapidly, but each needs a skilled user to maximize results obtained from these techniques. Multidisciplinary teams are therefore key to making optimal use of these methods and such qualified teams can provide enormous benefits to pharmaceutical companies to improve device efficacy and thus time to market. There is already a move to integrate the benefits of Industry 4.0 into inhaler design and usage, a trend that will accelerate.